The Influence of Mixed Filter Materials on the Performance of Biological Slow Filtration in Rainwater Treatment - Dawei Mu; Xiangzhen Meng; Huali Zhang; Zhi Luo (Applied Sciences)
Freshwater resources are scarce in tropical island areas. Treating rainwater to produce drinking water through biological slow filtration (BSF) technology can significantly alleviate the problem of freshwater shortages. The characteristics of the filter material are the key factors determining the decontamination performance of BSF technology. However, most existing studies focus on a single filter material. This study was conducted using volcanic rock and coconut shell activated carbon to compare their pollutant removal characteristics in slightly polluted rainwater during the early stage of BSF operation (from the start of operation to day 6, with the first sampling time being 48 h after operation) and during the stable stage (26 days later) and further explore the influence of their mixing ratio. The results show that in the early stages of operation, the pollutant removal performance of volcanic rock and coconut shell activated carbon is better than that of quartz sand. Among them, coconut shell activated carbon showed average removal rates for NH3-N, TOC, and Cr(VI) that were 6.72, 8.46, and 19.01 percentage points higher than those of volcanic rock, respectively, but its average turbidity removal rate decreased by 5.00%. The removal effect of the mixed filter material was enhanced through the synergistic adsorption mechanism, but most of the improvements were within the standard deviation range and did not exceed the removal range of the single filter material. When the mixing ratio was 1:3, the average total organic carbon removal rate of the filter material was 71.51 ± 0.64%, approximately 0.96 percentage points higher than that of coconut shell activated carbon (70.55 ± 0.42%). While coconut shell activated carbon showed the best removal effect among all single filter materials, this improvement was still within the standard deviation range.